Barriers to intersectoral working to improve health: A qualitative study. (13th September 2011) - Taylor-Robinson, DC*; Lloyd-Williams, F; Orton, L; Moonan, M; O'Flaherty, M; Capewell, S
Abstract : Background: The National Health Service (NHS) is undergoing dramatic changes. Currently established partnerships are thus likely to be significantly disrupted by the radical reforms outlined in the Public Health White Paper. We therefore explored the process of inter-sectoral working between public health and local authorities, in order to better understand the potential opportunities and threats associated with the proposed changes. Methods: In depth qualitative study employing 40 semi-structured interviews and three focus group discussions including 37 people. Participants were senior and middle grade public health decision makers working in Primary Care Trusts (PCTs), Local Authorities, Department of Health, academia, General Practice and Hospital Trusts. Results: Opportunities exist to harness the often passionate belief in joined up action across sectors, in order to improve public health outcomes. Structures and partnerships have been developed between health, local authorities and the third sector over the last decade. Furthermore, many successes have been cited, around issues such as joint commissioning of social care, and planning and regeneration. However, clear threats are visible. Firstly, these collaborative networks may be completely disrupted as the proposed changes unfold. Secondly, lessons may not be learned about the barriers to joined-up working. Some of the perceived barriers are generic, relating to organisational culture, such as a lack of shared values and language. Perhaps of more concern are the barriers identified in our study relating to complexity and macro issues. These include the inherent complexity of intersectoral collaboration for public health, and macro issues such as political and resource constraints. There is clear uncertainty and anxiety about the future of joint working relating to the availability and distribution of scarce and diminishing financial resources. Conclusions: Intersectoral working during the last decade has resulted in innovative approaches and increased effectiveness in achieving public health goals. Public health provision is now moving into a new era, with local authorities being the main public health provider. Our data therefore provide some interesting insights and possible directions for future intersectoral working. Relocation of public health to local authorities may lead to more effective joint working in terms of the relationship between the bodies that potentially influence some determinants of health. However, important barriers persist. It remains to be seen if these barriers can be addressed and overcome.